Age-related characteristics of spectral bioelectric activity of the trophotropic zone of the hypothalamus in female rats - V. V. Mukvych; V. P. Lyashenko; S. M. Lukashov (Regulatory Mechanisms in Biosystems, 2018)
The purpose of the study was to determine the functional state of the trophotropic zone of the hypothalamus in female rats of different age groups according to bioelectric activity indices. Experiments were carried out on non-linear white outbred female rats. Animals were divided into IV groups: I group (2.5 months) the juvenile puberty period, II group (eight months) the young age of the reproductive period, III group (fourteen months) the mature age of the reproductive period, IV group (21 months) rats of presenile age of the pronounced senile changes period. Rats of the studied groups underwent Electric Hypothalamus Test (EGtG) of the trophotropic zone. The prevalence of low-frequency components of EGtG in female rats of the juvenile age and the domination of bioelectric activity in the delta range of the investigated hypothalamic region is determined. The young age in females was marked by an increase in all values of normalized spectral power, except the theta-like activity, which in turn was characterized by a possible decrease in the indices. In female rats, from young to presenile age, a gradual increase in the share of absolute power of high-frequency components of EGtG was observed, which was manifested in the functional activation of desynchronizing effect on bioelectric activity of the investigated hypothalamic region. There was an increase in theta-like and beta-like activity while there was a reduction in the percentage of alpha and especially delta wave power. In the female rats of the presenile age, the delta-like activity indices slightly recovered and exceeded those of mature female rats, theta and alpha-like activities underwent a significant decline in values and were represented by the lowest values, while beta-like activity was observed at the highest rates. However, it was precisely the mature female rats that showed a significant predominance of beta-like activity, which is evidence of the powerful desynchronizing mechanisms functioning. Electrophysiological indices indicate synaptic plasticity growth deficiency in female rats of the youngest age and factors of its degradation in those of presenile age, respectively. The power and the desynchronization rhythms representation increase is characteristic of the most productive age period with the most developed neurosynapticplasticity inherent to it.